Uma reflexão sobre a alegria nos espaços-tempos da escola - Lopes, Tomires Campos (2006)
The present research investigates the presence of the joy in the school. For in such a way, I chose the space-times pertaining to school as the entrance, the recreation and the lessons of Physical Education. The joy was investigated other related aspects as the perception that pupils, professors and managers have regarding the joy, as it if manifest, as it is characterized and if they inside perceive it of the school. They serve of theoretical sustentation to the works of Snyders that deals with the joy, what it comes to constitute the deep cloth of of this work and those that argue related subjects as Gomes, Château, Kishimoto; the authors who argue the phenomena of the game, the toy, the ludicidade, playing as Huizinga, Gomes; some of the theoreticians of the Physical Education as Castellani, Santin, Freire, Darido; the theoreticians who deal with the pleasure, as Mihaly and Lowen; e some authors who deal with the qualitative research as Bogdan, Bicudo, Ludke & Andres. The used methodology was of the descriptive qualitative method. Twenty children, being ten of each sex, a director and two supervisors and, still, five professors of a school of Cuiabá had served as citizens. The instruments of collection of data had been the comment, the interviews and the images. The results had evidenced a predominance of the joy in space-times: in the lessons of Physical Education, followed of the recreation, the entrance and finally the exit of the school. The school if relieves to the joy, for many times. This joy does not interest solely the children, but also the professors and the team technique. The recreation shows a diversity of joy forms. Already in the lessons the lesson, the joy if showed as present in the activities contained in the planejamentos of the professors. For you discipline them, exists an installed paradigm of that some are for nature glad, however, this illusion if it undid in this research. The research disclosed that the pupils if feel in the school welfare, if not feeling there imprisoned. A referring conclusion to the Physical Education, is of that the joy if makes gift, however in distinct activities for each citizen. E that is not only for those on ones to the "game. It was also clearly that the objective conditions of work, if make devoid so that the professors develop its crafts content it.